The giant, O'Brien a novel - Mantel, Hilary 1952-2022 (Holt, 1998)
A sick Irish giant in 18th century London is offered money by an anatomist if he will bequeath his body. The giant refuses, he wants to enter heaven whole, but the anatomist gets the body anyway. A parable on man of myth versus man of science. By the author of Eight Months on Ghazzah Street.
Keywords: Giants -- Fiction; Irish -- England -- Fiction; Pathology; Irland; Ireland -- Fiction; Historical fiction